The Influence of Blockchain Technology on Civil Law Enforcement in the Digital Era - Febri Wiratama; Syahriati Fakhriah; Silvester Magnus Loogman Palit; I Putu Gede Abdi Sudiatmika; Rona Tanjung (Rechtsnormen: Journal of Law, 2024)
Background: Blockchain technology has emerged as a revolutionary tool with the potential to transform various sectors, including civil law enforcement. Its decentralized, transparent, and immutable nature offers new possibilities for enhancing legal processes, ensuring data integrity, and reducing fraud. Objective: This study aims to evaluate the influence of blockchain technology on civil law enforcement. The research focuses on understanding how blockchain can enhance legal processes, improve data security, and foster transparency within the civil law system. Methods: A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Quantitative data were collected from 200 legal professionals and law enforcement officers, measuring their perceptions of blockchain's impact on various legal processes. Qualitative interviews with 30 key stakeholders provided deeper insights into blockchain's practical applications and challenges in civil law enforcement.. Results: Findings indicate that blockchain technology can significantly enhance data security, transparency, and efficiency in civil law enforcement. Best practices identified include the use of smart contracts for automated enforcement and blockchain for secure evidence management. Challenges such as technical complexity, cost, and legal interoperability were also highlighted. Conclusion: Blockchain technology holds significant promise for improving civil law enforcement by enhancing transparency, security, and efficiency. Implementing best practices can optimize these benefits, although challenges remain.